Feasibility of multidisciplinary telehealth evaluations in atypical dementia. (31st December 2021) - Wong, Bonnie; Loyer, Emmaleigh; Sullivan, Courtney; Krivensky, Samantha; Lopez, Angela Villareyna; Quimby, Megan; Hochberg, Daisy; Dev, Sheena Isha; Putcha, Deepti; Eldaief, Mark C; Brandt, Katie; Dickerson, Brad C.
Abstract: Introduction: While cognitive assessment by videoconference has become possible over the past decade, the COVID‐19 pandemic underscores the critical need for expansion and examination of these methods, their appropriateness for various patient populations, and their benefits and limitations. Validity and reliability studies of tele‐neuropsychological testing have been conducted in MCI or mild AD dementia patients (e.g., MMSE=25+); few studies have assessed the feasibility of neurologic examination by video, and none in atypical dementias, assuming that patients with some types (e.g., language, comportment) or greater severity of cognitive‐behavioral impairment would be unable to participate. Here we report the feasibility of telehealth services for a multi‐disciplinary dementia subspecialty clinic that include cognitive‐behavioral and neurologic assessment with patients with atypical neurodegenerative syndromes. Methods: 104 patient‐carepartner (P‐C) dyads met with providers in the MGH FTD Unit by videoconference (March‐December, 2020) for routine clinical care. P‐Cs completed validated questionnaires assessing cognition‐mood/behavior/function on REDCap prior to video clinical interview and cognitive assessment, including the MoCA and Boston Cognitive Exam (BCE2.0), a newly revised brief cognitive assessment battery adapted for telehealth. P‐Cs met with a neurologist for a basic neurologic examination (including eye‐movement examination), review of assessment results, and discussion of care plan. P‐Cs completed a satisfaction survey. Results: The 104 P‐Cs included a range of atypical neurodegenerative disorders (bvFTD, PCA, PPA, CBS, PSP, eoAD, Multidomain syndrome) mild‐to‐severe impairment (CDR range: 0‐3). 76% completed the MoCA (25% had CDR=2). 36% also completed the BCEv2. Comparison of remote assessment data to previous in‐person testing is ongoing. Of P‐Cs who completed a satisfaction survey, all reported being "very satisfied" with the appointment, with 93% open to participating in a remote visit again. 87% found the telehealth visit comparable to an in‐person visit. 66% preferred a future combination of remote and in‐person visits. Conclusions: Multi‐disciplinary telehealth visits appear to be feasible with patients with atypical cognitive‐behavioral syndromes of across the severity spectrum. P‐Cs report a high degree of satisfaction with the telehealth visit and an openness to ongoing telehealth visits. Results have implications for increasing accessibility of multidisciplinary medical services for patients and families living with complex forms of dementia.